mIgM-mediated splenic marginal zone B cells targeting of folic acid for immunological evasion - Huan Wang; Zhuxuan Jiang; Zhiwei Guo; Gan Luo; Tianhao Ding; Changyou Zhan (Elsevier, 2024)
Folic acid is a fully oxidized synthetic folate with high bioavailability and stability which has been extensively prescribed to prevent congenital disabilities. Here we revealed the immunosuppressive effect of folic acid by targeting splenic marginal zone B (MZB) cells. Folic acid demonstrates avid binding with the Fc domain of immunoglobulin M (IgM), targeting IgM positive MZB cells in vivo to destabilize IgM-B cell receptor (BCR) complex and block immune responses. The induced anergy of MZB cells by folic acid provides an immunological escaping window for antigens. Covalent conjugation of folic acid with therapeutic proteins and antibodies induces immunological evasion to mitigate the production of anti-drug antibodies, which is a major obstacle to the long-term treatment of biologics by reducing curative effects and/or causing adverse reactions. Folic acid acts as a safe and effective immunosuppressant via IgM-mediated MZB cells targeting to boost the clinical outcomes of biologics by inhibiting the production of anti-drug antibodies, and also holds the potential to treat other indications that adverse immune responses need to be transiently shut off.